Analisis Wacana Kritis terhadap Penolakan Pembangunan IKN pada Wacana Berita Daring di Indonesia - Iffah, Rahmah Nur; Bachari, Andika Dutha; Fadlilah, Afi (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2025)
The study aims to describe the textual, social cognitive, and social contextual dimensions that represent rejection of the development of Ibu Kota Nusantara on the news portals Metrotvnews.com and Viva.co.id in December 2023. This is motivated by the widespread controversy surrounding the development of the new capital city, Ibu Kota Nusantara, among the public. This study employs a descriptive qualitative method, applying Teun van Dijk's Critical Discourse Analysis framework and Halliday's transitivity. The findings reveal that news discourse is constructed through specific topics and schemes related to the Ibu Kota Nusantara issue. Metrotvnews.com explicitly represents rejection by presenting the voices of various parties and aspects of society, thus reflecting a pro-citizen ideology. Meanwhile, Viva.co.id implicitly represents rejection, as it leans towards the dominant parties that support government policies. These differences in representation are closely related to social media cognition and the socio-political context towards the 2024 elections, which influence the production and dissemination of discourse to the public.